Southern African osmiine bees: taxonomic notes, two new species, a key to Wainia, and biological observations (Hymenoptera: Anthophila: Megachilidae) - Kuhlmann, Michael; Gess, Friedrich W.; Koch, Frank; Gess, Sarah K. (Zootaxa, 2011)
Resulting from the examination of the type specimens of the southern African bee species originally described in the genus Osmia, the taxonomic placement of 19 species is formally established. The following combinations are formalised: Osmia atrorufa Friese, 1913 to Wainia (Caposmia) atrorufa (Friese) comb. nov.; Osmia ausica Cockerell, 1944 to Hoplitis (Anthocopa) ausica (Cockerell) comb. nov.; Osmia capicola Friese, 1909 (replacement name for Osmia capensis Cameron, 1906) to Capicola capicola (Friese) comb. nov.; Osmia flavipes Friese, 1909 to Afranthidium (Nigranthidium) flavipes (Friese) comb. nov.; Osmia forficulina Cockerell, 1921 to Hoplitis (Anthocopa) forficulina (Cockerell) comb. nov.; Osmia karooensis Brauns, 1926 to Hoplitis (Anthocopa) karooensis (Brauns) comb. nov.; Osmia mediorufa Cockerell, 1932 to Hoplitis (Anthocopa) mediorufa (Cockerell) comb. nov.; Osmia namaquaensis Friese, 1913 to Hoplitis (Anthocopa) namaquaensis (Friese) comb. nov.; Osmia natalensis Cockerell, 1920 to Wainia (Caposmia) natalensis (Cockerell) comb. nov.; Osmia neavei Cockerell, 1936 to Hoplitis (Anthoc- opa) neavei (Cockerell) comb. nov.; Osmia ogilviae Cockerell, 1932 to Hoplitis (Anthocopa) ogilviae (Cockerell) comb. nov.; Osmia ornatula Cockerell, 1932 to Hoplitis (Anthocopa) ornatula (Cockerell) comb. nov.; Osmia orthodonta Cokkerell, 1932 to Hoplitis (Anthocopa) orthodonta (Cockerell) comb. nov.; Osmia pachyceps Friese, 1922 to Othinosmia (Megaloheriades) pachyceps (Friese) comb. nov.; Osmia piliventris Friese, 1913 to Hoplitis (Anthocopa) piliventris (Friese) comb. nov.; Osmia reginae Cockerell, 1932 to Hoplitis (Anthocopa) reginae (Cockerell) comb. nov.; Osmia rhodognatha Cockerell, 1932 to Hoplitis (Anthocopa) rhodognatha (Cockerell) comb. nov.; Osmia similis Friese, 1909 to Hoplitis (Anthocopa) similis (Friese) comb. nov.; Osmia turneri Cockerell, 1937 to Hoplitis (Anthocopa) turneri (Cockerell) comb. nov. The following new synonyms are established: Hoplitis (Anthocopa) namaquaensis (Friese) = Osmia ausica Cockerell syn. nov.; Capicola capicola (Friese) (replacement name for Osmia capensis Cameron) = Capicola braunsiana Friese, 1911 syn. nov., Capicola aurescens Cockerell, 1932 syn. nov., Hesperapis turneri Cockerell, 1934 syn. nov., Hesperapis obscura Cockerell, 1934 syn. nov.; Unlike the statement in Michener (2000: 403) Osmia? capensis Cameron, 1905 is probably not a synonym of Capicola braunsiana Friese given its body length. The type seems to be lost and the identity of this species remains unclear. Hoplitis (Anthocopa) similis (Friese) = Osmia forficulina Cockerell syn. nov; Wainia (Wainiella) sakaniensis (Cockerell, 1936) = Heriades albobarbatus Cockerell, 1937 syn. nov., Heriades debilicornis Cockerell, 1940 syn. nov., Heriades perpolitus Cockerell, 1947 syn. nov., Heriades otaviensis Cockerell, 1947 syn. nov. The status of Wainia (Caposmia) elizabethae (Friese, 1909) spec. rev. as a valid species is restored. Hoplitis (Anthocopa) conchophila Kuhlmann spec. nov., Wainia (Caposmia) gessorum Kuhlmann spec. nov. and the male of Wainia (Caposmia) atrorufa (Friese) are described for the first time. A checklist and an illustrated key to the seven southern African species of Wainia is provided. Notes on known flower visiting and nesting of Hoplitis (Anthocopa) and Wainia are given under the relevant species.